An Afghan Tragedy: The Pashtuns, the Taliban and the State. Issue 3 (4th May 2021) - Lieven, Anatol
Abstract : Whatever happens in Kabul, the Taliban will remain the most powerful military and political force among the Pashtuns of Afghanistan.